The interpretation of dreams - Freud, Sigmund, 1856-1939 (Oxford world's classics, 1999)
One hundred years ago Sigmund Freud published The Interpretations of Dreams, a book that, like Darwin's The Origin of Species, revolutionized our understanding of human nature. Now this groundbreaking new translation--the first to be based on the original text published in November 1899--brings us a more readable, more accurate, and more coherent picture of Freud's masterpiece. The first edition of The Interpretation of Dreams is much shorter than its subsequent editions; each time the text was reissued, from 1909 onwards, Freud added to it. The most significant, and in many ways the most unfortunate addition, is a 50-page section devoted to the kind of mechanical reading of dream symbolism--long objects equal male genitalia, etc.--that has gained popular currency and partially obscured Freud's more profound insights into dreams. In the original version presented here, Freud's emphasis falls more clearly on the use of words in dreams and on the difficulty of deciphering them. Without the strata of later additions, readers will find here a clearer development of Freud's central ideas--of dream as wish-fulfillment, of the dream's manifest and latent content, of the retelling of dreams as a continuation of the dreamwork, and much more. Joyce Crick's translation is lighter and faster-moving than previous versions, enhancing the sense of dialogue with the reader, one of Freud's stylistic strengths, and allowing us to follow Freud's theory as it evolved through difficult cases, apparently intractable counter-examples, and fascinating analyses of Freud's own dreams. The restoration of Freud's classic is a major event, giving us in a sense a new work by one of this century' most startling, original, and influential thinkers.